Migrant language and identity in the Spanish-speaking community in Israel - Fritzler Marcela (Journal of World Languages, 2023)
Spanish has a considerable presence in the socio-cultural mosaic of Israel, a country made up of ethnolinguistic communities from different parts of the world. However, language policy has not always integrated the study of languages as a source of interculturality. This paper summarizes the results of the first stage of a broader investigation into the linguistic practices and strategies developed by Spanish-speaking families to acquire and preserve the migrant language, as a way of transmitting the heritage, identity and culture of the country of origin in the face of the influence of the majority language, Hebrew. To this end, individual interviews were conducted to record specific data on the Spanish-speaking community and, particularly, the presence of Spanish as a vehicular language through the identification of sociocultural references among families who arrived under the Law of Return and include members who are 15 years of age or younger. The surveys reflect that the interest and affective need to preserve the language are main motivators in these Spanish-speaking families. These conclusions served as a basis for in the afore-mentioned group were considered relevant conclusions within the broad objectives of the larger project, which seeks to create a program of intergenerational activities to develop respectful bilingualism and strengthen the community of practice as a space to build the mutant puzzle between the inherited and acquired identity of children and youth.